Microbiological and immunological aspects related to the colonization and infection of patients by resistant Acinetobacter baumannii in nosocomial environment (Research, Society and Development, 2021)
Introduction: As we progress in the development of antimicrobials, we observe new forms of bacterial resistance due to the selectivity resulting from the irrational use of these drugs. A species emerges capable of causing serious infections, especially in a nosocomial environment: Acinetobacter baumannii. By producing resistance mechanisms, it adapts to less favorable means, which makes it the subject of worldwide debates regarding the future of antibiotic therapy as it is responsible for high annual mortality rates due to hospital infections. Despite this, there is a shortage of epidemiological data that promote awareness, especially in Brazil. Objective: To gather information about the immunological aspects resulting from colonization by this bacterium and defense mechanisms involved in cases of infected individuals. Methodology: Literature review through analysis of articles from Pubmed and Scielo banks, information was obtained on forms of transmission, associated diseases, immunological reactions caused and main forms of resistance. Results: Brazilian Intensive Care Units (ICUs) frequently detect cases of Health Care Related Infections (IRAS). In cases where the strains of Acinetobacter baumannii are responsible, they usually show resistance to the available antimicrobials, causing high financial costs in the treatment and a mortality rate of approximately 47% due to the immunological fragility and carrying out invasive procedures. Conclusion: The patient colonized by A. baumannii becomes an agent of indirect transmission of pathogen to the hospital environment and infections are severe, therefore, elucidating the modes of transmission and resistance profile is of extreme clinical and epidemiological relevance, considering the scarcity of epidemiological data.